2016
DOI: 10.1186/s12879-016-1915-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia trachomatis infection in women, heterosexual men and MSM visiting HIV counselling institutions in North Rhine-Westphalia, Germany - should Chlamydia testing be scaled up?

Abstract: BackgroundPatients asking for a free anonymous HIV test may have contracted other sexually transmitted infections (STIs) such as Chlamydia trachomatis, yet Chlamydia prevalence in that population is unknown. This study aimed to assess the prevalence and factors associated with Chlamydia infection in patients seeking HIV testing at local public health authorities (LPHA) in order to evaluate whether Chlamydia testing should be routinely offered to them.MethodsWe conducted a cross-sectional study among patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
6
15
2
Order By: Relevance
“…Three of the four cases (75%) of C. trachomatis encoun-tered in this study, were asymptomatic, which is similar to 76.7% reported by Lallemand et al (6). Similarly, some of the girls that harbored other potentially pathogenic organisms did not manifest any symptoms, even in situations where multiple organisms were recovered in the vagina.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Three of the four cases (75%) of C. trachomatis encoun-tered in this study, were asymptomatic, which is similar to 76.7% reported by Lallemand et al (6). Similarly, some of the girls that harbored other potentially pathogenic organisms did not manifest any symptoms, even in situations where multiple organisms were recovered in the vagina.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, some of the girls that harbored other potentially pathogenic organisms did not manifest any symptoms, even in situations where multiple organisms were recovered in the vagina. Asymptomatic or mildly symptomatic nature of urogenital pathogens, such as Chlamydia, may allow the infection to go unnoticed until secondary or tertiary symptoms develop and could lead to serious complications and/or sequelae (6,8). The asymptomatic carriage of the organisms coupled with reported high coital activity among teenagers in Nigeria (14), may result in indiscriminate transmission of the carried organisms to sexual partners, who may also pass it along to subsequent sexual partners -extending the transmission chain; this transmission chain could continue to grow until a symptomatic contact is involved or tertiary complications cause a victim to seek treatment, or diagnosis occurs after a universal screening exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of chlamydia and gonorrhea infections, Dudareva-Vizule and colleagues estimated that the prevalence of these two STI in men having sex with men ranged from 1.5% to 8.0% depending on the anatomical site where samples were collected [4]. These findings were later corroborated by a study conducted in North Rhine-Westphalia in which chlamydia infection was found in 3.2% of heterosexual men and 3.5% of homosexual men [5]. Regarding trichomoniasis, no recent works have analyzed the prevalence of this STI in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…In Western Australia, the incidence of chlamydia has risen by 193% in the last decade, with 11,807 new cases reported in 2016 alone [ 1 ]. The asymptomatic nature of chlamydial infections in up to 70–90% of women and over 50% of men leaves the control of infections challenging [ 2 ]. If left untreated, chlamydial infections may lead to a number of severe, and possibly permanent, sequelae [ 3 ].…”
Section: Introductionmentioning
confidence: 99%